WINGKO BABAT DALAM E-COMMERCE (Information Technology and Telematics, 2014)
Abstract Sales Information System wingko tripe is a sales information system that produces a variety of information that can Bargunato support sales activitiesin Wingko Tripe Mr.Moel. The realization of the development of Information Systems Sales Wingkot his tripe is making the web that can represent the information system that is designed as a whole. Web generated sales wingko tripe able to manageand display information about wingko tripethatis sold a long with the price, purchase, transaction and sales reports. In conducting the analysis and design of this new system, the authoruses the method development SDLC(System Development Life Cycle). Meanwhile, to makethe process ofanalysis, the authors used object-oriented system susing design toolsis UML(Unified Modeling Language) which consists of the Use Case, Class Diagram, Activity Diagram, State Diagram and Sequence Diagram. From the analysis and design, information systems produced a web-based sales wingko tripe that can help Wingko Tripe Mr.Moe lin the process of promotion and sale of shoes effectively andefficiently. Keywords: Sales, WingkoTripe, Web